Androgen Deprivation Therapy and the Risk for Inguinal Hernia: An Observational Nested Case Control Study. Issue 6 (December 2021) - Hermann, Maria; Vikman, Hanna; Stattin, Pär; Katawazai, Asmatullah; Gustafsson, Ove; Styrke, Johan; Sandblom, Gabriel
It has been suggested that hypogonadism increases the risk for inguinal hernia (IH). The aim of this study was to investigate any association between androgen deprivation therapy (ADT) for prostate cancer and increased risk for IH. The study population in this population-based nested case-control study was based on data from the Prostate Cancer Database Sweden. The cohort included all men with prostate cancer who had not received curative treatment. Men who had been diagnosed or had undergone IH repair ( n = 1, 324) were cases and controls, where not diagnosed, nor operated on for IH, matched only on birth year ( n = 13, 240). Conditional multivariate logistic regression models were used to assess any temporal association between ADT and IH, adjusting for marital status, education level, prostate cancer risk category, Charlson Comorbidity Index, ADT, time since prostate cancer diagnosis, and primary prostate cancer treatment. Odds ratio (OR) for diagnosis/repair of IH 0 to 1 year from start of ADT was 0.5 (95% confidence interval [CI] = [0.38, 0.68]); between 1 and 3 years after, the OR was 0.35 (95% CI = [0.26, 0.47]); between 3 and 5 years after, the OR was 0.39 (95% CI = [0.26, 0.56]); between 5 and 7 years after, the OR was 0.6 (95% CI = [0.41, 0.97]); and >9 years after, the OR was 3.68 (95% CI = [2.45, 5.53]). The marked increase in OR for IH after 9 years of ADT supports the hypothesis that low testosterone levels increase the risk for IH. The low risk for IH during the first 8 years on ADT is likely caused by selection of men with advanced cancer unlikely to be diagnosed or treated for IH.